TINJAUAN YURIDIS PENANGANAN TINDAK PIDANA HOAX DAN UJARAN KEBENCIAN (HATE SPEECH) MELALUI MEDIA SOSIAL - Pinasty Asyiah; Hamrin Hamrin (Muadalah : Jurnal Hukum, 2021)
The handling/efforts carried out by the Sorong City Police Criminal Investigation Unit against the crime of hoaxes and hate speech in the Sorong City area, namely through law enforcement efforts in accordance with applicable legal provisions as stipulated in the ITE Law, Criminal Code, and Criminal Procedure Code and the stages of handling them starting from the existence of a Police Report, Investigation, Summoning, Arrest, Detention, Search, Confiscation, Examination of Letters, then to the process of Submission of Case Files, Suspects, Witnesses and other Evidence to the Sorong District Attorney to be charged in Court.